A decade of WhatsApp: New production routines enable zapkeeper and audience newsmaking - Saback de Sá Moraes, Lilian (2019)
This paper proposes a close observation for journalism in the era of WhatsApp from the follow up of the program from April 8 to 12, 2019 of “Jor- nal BandNews Rio – 1ª Edição”, a radio news programme. From the thinking of researchers such as Lage (2001), Traquina (2005), Castells (2015), Wolf (1985) and Aguiar (2014), the study strains around classic theories such as newsmaking and gatekeeper in contemporary times. In conclusion, it presents the changes in the routines of press professionals that make it possible to think about the emergence of zapkeeper and audience newsmaking.